(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The epithet, as a stylistic device, holds a significant place in literary texts. Its ability to enrich language and deepen meaning makes it a powerful tool for writers. This paper explores the concept of epithet, its various classifications, and its semantic roles within literary contexts. The study provides an in-depth semantic analysis of epithets by examining their contribution to imagery, emotional appeal, and stylistic nuance in selected literary works.